Increasing Conductivity in Proton Conductors BaCeO3-d doped with Pr - Basbus, Juan Felipe (2013)
In this work we explore the effect of partial substitution of Ce for Pr ions in BaCe1-xPrxO3-δ (0 ≤ x ≤0.8) perovskites with the aim of increasing the oxygen vacancies concentration and H+ charge carriers. The oxides were obtained by Pechini combustion method and sintered at 1350°C. The Pr incorporation improves the capability of to obtain dense samples at this temperature. Crystal structure were studied by X-ray diffraction, while morphology by SEM. The conductivity was studied by Electrical Impedance Spectroscopy (EIS) under 20 % O2/Ar and 10 % H2/Ar, both with 2% humidity. We found that the Pr content diminished the lattice parameters, increase the sintering capacity and the conductivity under wet oxidant atmosphere, but it decreases the stability under reducing atmosphere